Ethical aspects of information literacy in artificial intelligence - Ottonicar, Selma Leticia Capinzaiki [UNESP]; Manhique, Ilídio Lobato Ernesto [UNESP]; Mosconi, Elaine (IGI Global, 2020)
The purpose is to analyse information literacy to provide ethical insight into artificial intelligence. The methodology was based on a systematic literature review of SCOPUS, Web of Science, Library and Information Science Abstracts, and Science Direct. The results demonstrated that there are only a few studies about the topic, so there is a research opportunity about this type of literacy and its ethical aspects in the context of artificial intelligence. As a conclusion, information literacy is crucial to the development of critical thinking in technology use. Information literacy should be applied in artificial intelligence courses to discuss ethical aspects of technology.